Drag Losses of Wet Brakes and Clutches—A Scoping Review - Lukas Pointner-Gabriel; Katharina Voelkel; Karsten Stahl (Lubricants)
Wet brakes and clutches are crucial drivetrain components widely used in many sectors. However, their drag losses can account for a considerable share of the overall drivetrain losses. Therefore, investigation of the drag loss behavior of wet brakes and clutches has been the subject of research since the 1970s. This paper aims to provide a comprehensive overview of existing knowledge of drag loss behavior and identify future research directions. To this end, a scoping review was conducted according to the PRISMA guideline. It was found that research mainly, but not only, focused on gaining a fundamental understanding of the drag loss generation process, investigating the integral drag loss behavior, analyzing the flow in the sub-millimeter gaps, and modeling and calculating the drag losses. The review summarizes the state of the art and may support researchers and engineers in developing low-loss wet brake and clutch systems. Several research gaps were identified and are provided.